Dual Monetary System and Macroeconomic Performance in Indonesia - Sri Herianingrum; Imronjana Syapriatama (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
This research aims to evaluate the impact of dual monetary policyshock on macroeconomic indicators of Indonesia: growth and inflation. Inaddition, this study will also examine whether conventional monetary policy hasa particular impact upon Islamic banking sector. This research apply VAR (vectorauto regressive) method on monthly data from Bank Of Indonesia during theperiod of January 2010 to December 2013. The result of IRF explain that theinterest rate channel find the hard way to accomplished the macroeconomic goalswhile the Islamic monetary instrument indicates the potential growth of outputand hold the inflation low. The result of VDC describes that the Islamic instrumentstill affected by conventional monetary policy because of slow development inIslamic monetary systemDOI: 10.15408/aiq.v8i1.2509